Freedom Behind Bars: The central role of emotions in naturalizing an analogy for social change. Issue 10 (October 2022) - Farchi, Tomás; Logue, Danielle; Fernández, Pablo; Vassolo, Roberto
In this paper we examine how a socially innovative solution to a complex social problem is able to overcome entrenched disadvantage and division and sustain itself within an existing institution. We explore how a rugby team in a high-security prison in Argentina has become an organizational response that substantially transformed prisoners' lives in and out of jail, allowing inmates to reclaim many critical aspects of their humanity and dramatically reducing recidivism. We examine rugby as an analogy for new models of behaviours and identities in the context of extreme disadvantage, and surface the specific emotional work required to make the analogy generative. The findings from our in-depth case study reveal three reinforcing mechanisms in the workings of an analogy – resonating, resignifying and collective generativity – and in doing so provide a novel crescive model of how analogies may sustain change emotionally, cognitively and behaviorally over time, and ultimately achieve positive transformational effects in extreme social contexts.